1970
DOI: 10.1063/1.1673042
|View full text |Cite
|
Sign up to set email alerts
|

Viscosities of the Inert Gases at High Temperatures

Abstract: The viscosities of the inert gases and nitrogen have been determined over the temperature range 300–1600°K. The results suggest that earlier measurements are in error by as much as 6% at 1600°K. The extent to which the new results may lead to a revision of the functions commonly used to represent the intermolecular energy of simple molecules is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(68 citation statements)
references
References 37 publications
6
61
1
Order By: Relevance
“…These systematic deviations are a consequence of a temperature measurement error with thermocouples extensively discussed by Vogel et al [69] and are still relatively small for helium due to the large thermal conductivity coefficient compared with those of other common gases. The relative measurements of Guevara et al [66] and of Dawe and Smith [67] with capillary viscometers based on a reasonable calibration at room temperature make obvious that they are influenced by systematic errors and that the theoretical calculation is distinctly superior to the experiment at these high temperatures. Figure 8 displays the deviations of the experimental viscosity data by Becker et al [57] and Becker and Misenta [58] from the theoretically calculated values for 3 He.…”
Section: To Higher Values With Increasing Temperature But This Tendementioning
confidence: 99%
“…These systematic deviations are a consequence of a temperature measurement error with thermocouples extensively discussed by Vogel et al [69] and are still relatively small for helium due to the large thermal conductivity coefficient compared with those of other common gases. The relative measurements of Guevara et al [66] and of Dawe and Smith [67] with capillary viscometers based on a reasonable calibration at room temperature make obvious that they are influenced by systematic errors and that the theoretical calculation is distinctly superior to the experiment at these high temperatures. Figure 8 displays the deviations of the experimental viscosity data by Becker et al [57] and Becker and Misenta [58] from the theoretically calculated values for 3 He.…”
Section: To Higher Values With Increasing Temperature But This Tendementioning
confidence: 99%
“…Experiments are from: /: [34], /: [85], / : [86], and /: [87]. Experiments are from: /: [36], /: [34], /: [85], and /: [81]. …”
Section: Tablesmentioning
confidence: 99%
“…This demonstrates that the measurements by Vogel with his all-quartz oscillating-disc viscometer represent the best experiments in this temperature range. The comparison concerning the experimental data by Dawe and Smith [39] and by Guevara and Stensland [40], which result from relative measurements with capillary viscometers based on a reasonable calibration at room temperature, shows that these data should be influenced by systematic errors. Lastly it is concluded that the theoretical determination of viscosity values is to be preferred to experiments at these high temperatures.…”
Section: Viscositymentioning
confidence: 99%
“…Deviations of experimental and calculated viscosity coefficients from values cal(pres) calculated with the new interatomic potential for Ne at higher temperatures. Experimental data with uncertainties characterized by error bars: 5 Kestin et al [27], best estimate; Hellemans et al [37]; Kestin et al [38]; s Dawe and Smith [39]; oe Guevara and Stensland [40]; i Vogel [29], fitted values; m Vogel [29], experimental data corrected according to new helium standard. Calculated values: Á Á Á Á Á Á Á Á Á fifth-order classical calculation [] cl,5 ; ----potential by Aziz and Slaman [7]; -Á -Á -Á potential by Cybulski and Toczylowski [6]; ----potential by Wu¨est and Merkt [5].…”
Section: Viscositymentioning
confidence: 99%